Quadratic Equations: Solve when factorised Silent Teacher Intelligent Practice Narration Your Turn (𝑥−6)(𝑥−3)= (𝑥−6)(𝑥−2)= (2𝑥−6)(𝑥−2)= Example For more videos visit mrbartonmaths.com/videos
Worked Example Your Turn (𝑥+3)(𝑥−4)=0 (𝑥−3)(𝑥+4)=0 @mrbartonmaths
(𝑥+6)(𝑥+3)=0 (2𝑥+6)(𝑥−2)=0 (𝑥+3)(𝑥+6)=0 (𝑥+6)(2𝑥−2)=0 (𝑥−3)(𝑥+6)=0 (𝑥+6)(2𝑥−3)=0 (𝑥−6)(𝑥+3)=0 (𝑥+6)(2𝑥−5)=0 𝑥−6 𝑥−3 =0 𝑥+6 5𝑥−2 =0 (𝑥−6)(𝑥−2)=0 (7𝑥+6)(5𝑥−2)=0 2𝑥−6 𝑥−2 =0 7𝑥−6 5𝑥+2 =0 @mrbartonmaths
(𝑥+6)(𝑥+3)=0 (2𝑥+6)(𝑥−2)=0 (𝑥+3)(𝑥+6)=0 (𝑥+6)(2𝑥−2)=0 (𝑥−3)(𝑥+6)=0 𝑥=−6 𝑥=−3 𝑥=−3 𝑥=2 (𝑥+3)(𝑥+6)=0 (𝑥+6)(2𝑥−2)=0 𝑥=−3 𝑥=−6 𝑥=−6 𝑥=1 (𝑥−3)(𝑥+6)=0 (𝑥+6)(2𝑥−3)=0 𝑥=3 𝑥=−6 𝑥=−6 𝑥=1.5 (𝑥−6)(𝑥+3)=0 (𝑥+6)(2𝑥−5)=0 𝑥=6 𝑥=−3 𝑥=−6 𝑥=2.5 𝑥−6 𝑥−3 =0 𝑥+6 5𝑥−2 =0 𝑥=6 𝑥=3 𝑥=−6 𝑥= 2 5 (𝑥−6)(𝑥−2)=0 (7𝑥+6)(5𝑥−2)=0 𝑥=− 6 7 𝑥= 2 5 𝑥=6 𝑥=2 2𝑥−6 𝑥−2 =0 7𝑥−6 5𝑥+2 =0 𝑥=3 𝑥=2 𝑥= 6 7 𝑥=− 2 5 @mrbartonmaths